Model For Improving Student Learning Outcomes Based on Facilities, Infrastructure, And Teacher Performance at MA Minhajut Tholabah - Bawono Pambarep Putro; Widiyanto Widiyanto; Fakhruddin Fakhruddin (Eduvest - Journal of Universal Studies, 2026)
Education is one of the main factors in improving the quality of human resources. The improvement of student learning outcomes is not only influenced by individual abilities, but also by the availability of adequate facilities and infrastructure as well as optimal teacher performance. MA Minhajut Tholabah as an Islamic boarding school-based educational institution in Purbalingga Regency faces challenges related to limited facilities and the need to improve teacher professionalism. This condition encourages the importance of research on models of improving student learning outcomes based on facilities and infrastructure as well as teacher performance. This study uses a qualitative approach with a descriptive method. Data was obtained through observation, interviews, and documentation involving madrasah heads, teachers, and students as the main data sources. Data analysis is carried out by data reduction techniques, data presentation, and conclusion drawn, accompanied by triangulation to ensure the validity of the data. The focus of the research is directed at the identification of the condition of facilities and infrastructure, management evaluation, and the role of teacher performance in improving student learning outcomes. The results of the study show that the facilities and infrastructure at MA Minhajut Tholabah are still mostly limited, especially laboratories and libraries. However, these limitations can be overcome with proper management and support from the school and committee. Teacher performance has been proven to have a significant effect on motivation and achievement of student learning outcomes, especially through varied learning strategies and character strengthening.